Prevalence of gestational diabetes mellitus in the Greater Giyani Area, Mopani District, Limpopo Province - Ntshauba, Elelwani Thelma (My University, 2020)
The purpose of this study was to determine the prevalence of gestational diabetes mellitus (GDM) and the associated risk factors in the Greater Giyani Area, Mopani District. Quantitative cross-sectional descriptive study was conducted to determine the prevalence rate and risk factors of GDM. Data was collected using questionnaire and data entry form. One hundred and one (101) pregnant women who were attending antenatal clinic visits at Nkhensani Hospital, Nkhensani Gateway Clinic and Giyani Healthcare Centre participated in the study. The SPSS programme was used and p-value of <0.05 was considered significant. The study found that the prevalence of GDM in the area was 1.9%. Pregnant women above 30 years with secondary education, employed, obese and at gestational age of 31-35 weeks were more likely to present with GDM. A family history of diabetes was significantly associated with development of GDM. In conclusion, the universal screening approach for GDM needs to be adopted by all health institutions.
Thesis (MPH.) -- University of Limpopo, 2020
Keywords: Gestational diabetes mellitus; Prevalence; Risk factors; Diabetes in pregnancy; Pregnancy -- Complications